2018
DOI: 10.1515/agms-2018-0009
|View full text |Cite
|
Sign up to set email alerts
|

Inradius Estimates for Convex Domains in 2-Dimensional Alexandrov Spaces

Abstract: We obtain sharp lower bounds on the radii of inscribed balls for strictly convex isoperimetric domains lying in a 2-dimensional Alexandrov metric space of curvature bounded below. We also characterize the case when such bounds are attained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…For 2-dimensional λ-convex bodies in the Euclidean plane, i.e., the space of constant zero curvature, Milka [Mi2] proved that the λ-convex lens has the smallest inradius for a given length of the boundary. Much later, this result was generalized in [Dr4] to arbitrary λ-convex domains in 2-dimensional Alexandrov spaces of curvature bounded below, thus closing this question in dimension 2. Recently, Bezdek [Be1] showed that among all λconvex bodies in R n , n 2, the λ-convex lens has the smallest inradius for a given volume.…”
mentioning
confidence: 98%
“…For 2-dimensional λ-convex bodies in the Euclidean plane, i.e., the space of constant zero curvature, Milka [Mi2] proved that the λ-convex lens has the smallest inradius for a given length of the boundary. Much later, this result was generalized in [Dr4] to arbitrary λ-convex domains in 2-dimensional Alexandrov spaces of curvature bounded below, thus closing this question in dimension 2. Recently, Bezdek [Be1] showed that among all λconvex bodies in R n , n 2, the λ-convex lens has the smallest inradius for a given volume.…”
mentioning
confidence: 98%